Preparedness of public health-care system for Zika virus outbreak: An Indian perspective - Nivedita Gupta; Pragya D. Yadav; Deepak Y. Patil; Gajanan Sapkal (Elsevier, 2020)
Zika virus is a mosquito-borne flavivirus that has emerged recently and affected in many countries. Since its discovery in Uganda in 1947, two major outbreaks were reported from Yap Islands in 2007 and French Polynesia in 2013. In 2015, the first case of ZIKV infection was confirmed from Brazil followed by a report of cases from American and Caribbean countries. In February 2016, the World Health Organization declared ZIKV infection a Public Health Emergency of International Concern. India reported the first Zika case in 2017. Subsequently, 157 laboratory-confirmed cases of ZIKV including 63 pregnant women were reported from Rajasthan, India in 2018. Since 2014, many countries took initiatives to boost their public health system to combat ZIKV. However, there is still scope for the improvement. This review describes ZIKV outbreaks, diagnostic challenges, surveillance and control measures in India and the future perspective to deal with the ZIKV outbreak in India.